Is There an Early Gender Gap in School Readiness Among 3-4-year-old Children? Evidence from Ghana - Jean Louis Bago; Moussa Ouédraogo; Marie Madeleine Ouoba (İktisat Politikası Araştırmaları Dergisi)
Gender inequalities in education persist in developing countries, but comprehensive policies to address them are often lacking. Using microlevel data from Ghana’s Multiple Indicator Cluster Survey (MICS), we investigated the presence of an early gender gap in school readiness among 3-4-year-old children. First, we built two multidimensional indexes of school readiness that account for children’s ability to read, count, recognise numbers, interact with peers and others, follow rules and be independent for their health outcomes and physical skills. Second, we estimated the gender gap while controlling for factors affecting school readiness using regional fixed effects. We found no evidence of a gender difference in children’s school readiness. This result is robust to several specifications and sensitivity tests. In contrast, the results showed that a mother’s education, a father’s involvement and the fact of living in an urban area are positively associated with school readiness for both boys and girls. Based on these findings, we argue that the educational gender gap in Ghana most likely reflects the unequal access to schooling opportunities between boys and girls. Hence, policy makers should target the barriers in school access for both boys and girls to achieve educational gender equity.